Regulation of Transplanted Cell Homing by FGF1 and PDGFB after Doxorubicin Myocardial Injury - Mark Baguma-Nibasheka (MDPI AG, 2021)
There is no effective treatment for the total recovery of myocardial injury caused by an anticancer drug, doxorubicin (Dox). In this study, using a Dox-induced cardiac injury model, we compared the cardioprotective effects of ventricular cells harvested from 11.5-day old embryonic mice (E11.5) with those from E14.5 embryos. Our results indicate that tail-vein-infused E11.5 ventricular cells are more efficient at homing into the injured adult myocardium, and are more angiogenic, than E14.5 ventricular cells. In addition, E11.5 cells were shown to mitigate the cardiomyopathic effects of Dox. In vitro, E11.5 ventricular cells were more migratory than E14.5 cells, and RT-qPCR analysis revealed that they express significantly higher levels of cytokine receptors Fgfr1, Fgfr2, Pdgfra, Pdgfrb and Kit. Remarkably, mRNA levels for Fgf1, Fgf2, Pdgfa and Pdgfb were also found to be elevated in the Dox-injured adult heart, as were the FGF1 and PDGFB protein levels. Addition of exogenous FGF1 or PDGFB was able to enhance E11.5 ventricular cell migration in vitro, and, whereas their neutralizing antibodies decreased cell migration. These results indicate that therapies raising the levels of FGF1 and PDGFB receptors in donor cells and or corresponding ligands in an injured heart could improve the efficacy of cell-based interventions for myocardial repair.